Maria de Lourdes Vale Nascimento and racism in the dawn of Social Work - Gonçalves, Renata; Lira, Priscila Lemos (Argumentum, 2024)
This article problematises the conservative and moralistic agenda of the first Brazilian social workers, who had difficulty understanding the complexity of the relationships between capitalist class exploitation and racism. As a form of resistance, Black organisations such as the Frente Negra Brasileira (Brazilian Black Front) emerged, with a Department of Women that aimed to prepare Black women to survive in a racist society. With the end of social and political organisations, imposed by the Estado Novo (New State) dictatorship, discussions about racism in Brazil were only openly resumed later. Maria de Lourdes Vale Nascimento, possibly one of the first Black social workers in the country, emerged to counter conservatism and lead the struggle for the labour rights of domestic workers, the majority of whom are Black. This study is the result of bibliographic and documentary research, particularly of publications from the Black press, such as the newspaper Quilombo (1948-1950) and the movimentos negros (Black movements). We consider such material to be an important source for research yet to be explored regarding Social Work.